Antibacterial effect of nisin in vitro - Marina M. Mishina; Andrey N. Burov; Vitaliy A. Vekshin; Evgeniya R. Grabovetskaya (Kazimierz Wielki University, 2020)
Results of experimental studies of antimicrobial action of gel compositions containing active substance nisin are presented in the article. It is shown that increasing concentration of nisin at constant concentrations of the other components in the mixture inhibits growth of Staphylococcus aureus and Pseudomonas aeruginosa. The optimal concentration of nisin at which the process of pathogens growth inhibition is the most effective was determined in the experiment.